CAZyme from gut microbiome for efficient lignocellulose degradation and biofuel production - Chettri, Dixita; Nad, Susmita; Konar, Ujjal; Verma, Anil Kumar (Frontiers in Chemical Engineering, 2022)
Over-exploitation and energy security concerns of the diminishing fossil fuels is a challenge to the present global economy. Further, the negative impact of greenhouse gases released using conventional fuels has led to the need for searching for alternative biofuel sources with biomass in the form of lignocellulose coming up as among the potent candidates. The entrapped carbon source of the lignocellulose has multiple applications other than biofuel generation under the biorefinery approach. However, the major bottleneck in using lignocellulose for biofuel production is its recalcitrant nature. Carbohydrate Active Enzymes (CAZymes) are enzymes that are employed for the disintegration and consumption of lignocellulose biomass as the carbon source for the production of biofuels and bio-derivatives. However, the cost of enzyme production and their stability and catalytic efficiency under stressed conditions is a concern that hinders large-scale biofuel production and utilization. Search for novel CAZymes with superior activity and stability under industrial condition has become a major research focus in this area considering the fact that the most conventional CAZymes has low commercial viability. The gut of plant-eating herbivores and other organisms is a potential source of CAZyme with high efficiency. The review explores the potential of the gut microbiome of various organisms in the production of an efficient CAZyme system and the challenges in using the biofuels produced through this approach as an alternative to conventional biofuels.